Public research organizations’ interactions with firms: factors driving the perceived benefits (2023)
This paper investigates which factors are more effective when taking advantage of benefits perceived by firms in their collaborations with public research organizations (PROs). The empirical study is based on a survey of firms that have collaborated with the Spanish National Research Council (CSIC), the largest PRO in Spain. We performed an ordinal probit regression, where the dependent variables reflect the importance of benefits from the interaction. We add to previous literature by considering benefits beyond innovation results and by studying the firm´s absorptive capacity and knowledge search strategy as determinants of such benefits. Our results show that firms need to have a certain level of absorptive capacity to take advantage of the collaboration with PROs, but that R&D is not the only antecedent that must be considered. Prior collaborative experience with PROs appears as an important factor to exploit these interactions, in particular as a way to develop internal capabilities and obtain long-term benefits. The study also outlined the firm´s external search strategy as a relevant factor in determining the benefits obtained from interactions with PROs.